The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1519/jsc.0000000000001194
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Attentional Focusing Instructions on Force Production During the Isometric Midthigh Pull

Abstract: Verbal instructions play a key role in motor learning and performance. Whereas directing one's attention toward bodily movements or muscles (internal focus) tends to hinder performance, instructing persons to focus on the movement outcome, or an external object related to the performed task (external focus) enhances performance. The study's purpose was to examine whether focus of attention affects maximal force production during an isometric midthigh pull (IMTP) among 18 trained athletes (8F & 10M). Athletes p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
99
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(104 citation statements)
references
References 24 publications
1
99
1
Order By: Relevance
“…Once body position was stabilized (verified by watching the participant and force trace), the participants were given a countdown of "3, 2, 1, Pull!". Minimal pre-tension was permitted to ensure there was no slack in the participant's body prior to initiation of the pull, with the instruction to pull against the bar "as fast and hard as possible" (24), and push the feet down into the force plate; this instruction has been previously found to produce optimal testing results (23). Each IMTP trial was performed for approximately five seconds, and all participants were given strong verbal encouragement during each trial.…”
Section: Isometric Mid-thigh Pull Assessmentmentioning
confidence: 99%
“…Once body position was stabilized (verified by watching the participant and force trace), the participants were given a countdown of "3, 2, 1, Pull!". Minimal pre-tension was permitted to ensure there was no slack in the participant's body prior to initiation of the pull, with the instruction to pull against the bar "as fast and hard as possible" (24), and push the feet down into the force plate; this instruction has been previously found to produce optimal testing results (23). Each IMTP trial was performed for approximately five seconds, and all participants were given strong verbal encouragement during each trial.…”
Section: Isometric Mid-thigh Pull Assessmentmentioning
confidence: 99%
“…Of the limited research available, most studies use guideline instructions such as "pull hard and fast" when instructing participants during an isometric midthigh pull (2,10,13,29). Recently, Halperin et al (11) examined the focus of attention during an isometric midthigh pull in trained athletes. Participants completed trials in 3 different conditions for 3 consecutive days.…”
Section: Isometric Midthigh Pullmentioning
confidence: 99%
“…Halperin et al (11) concluded that an externally focused verbal instruction should be given to athletes when completing an isometric midthigh pull and consistency should be maintained with verbal instructions across testing days.…”
Section: Isometric Midthigh Pullmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, instructing participants to focus on the movement of their wrist during a basketball shot hinders accuracy, when compared with focusing on the basket [3]. Superior performance with EF is observed with tasks requiring large power output, such as long jump [4], sprint running [5], and in tasks requiring maximal force such as single joint elbow flexion [6], and multi-joint exercises, such as the isometric mid-thigh pull [7]. While preference for instructions/focus conditions has been shown to have a small effect on performance [8, 9], the benefits of EF are consistent across tasks, skill level, and age groups [2].…”
Section: Introductionmentioning
confidence: 99%